Explaining the increased German credit spread: The role of supply factors - Alessio J. G. Brown; Žiga Žarnić (Kiel Institute for World Economics (IfW), 2003)
Since 1999 an increase in magnitude and volatility of the credit spread is observable in the German bond market. This paper analyses the credit spread of German industrial bonds focussing on the one hand on the recent period of high volatility of the credit spread and on the other hand on possible influences of structural demand and supply effects. Our empirical estimation is conducted using an Error Correction Model (ECM) for a dataset of monthly time series from 1970 to 2003. We provide evidence on a significant impact of supply effects on the credit spread. Our in-sample forecasts trace the volatility of the credit spread surprisingly well.
Keywords: 330; Industrieobligation; Zinsstruktur; Risikoprämie; Rentenmarkt; Angebot; Bias; Schätzung; Deutschland